Engineering impacts on river channels in the river Rhine catchment - Herget, Jürgen; Bremer, Eckhard; Coch, Thomas; Dix, Andreas; Eggenstein, Georg; Ewald, Klaus (ERDKUNDE, 2005)
Due to the central location of the river Rhine catchment the channels are used for navigation for millennia. Local cliffs and bars lead simultaneously to measures for the improvement of the navigation and even construction of artificial channels as early as 12 BC. By a closer look, five periods of intensified modifications of the river channels and floodplains can be identified. The spectrum of engineering impacts is presented in a review and additionally illustrated by three examples from key locations: the so-called “Binger Loch” demonstrates the development of measures on one specific location throughout time, the rectification of the upper Rhine River exemplifies a more complex location where the channel and floodplains were shaped in combination while postulated measures nearly 2,000 years ago at the River Lippe catchment indicate engineering activities on river channels already in Antique times.